1999
DOI: 10.1016/s0886-3350(99)80078-9
|View full text |Cite
|
Sign up to set email alerts
|

Viscocanalostomy for open-angle glaucoma in black African patients

Abstract: Viscocanalostomy produced an encouraging long-term reduction in the IOP of black African patients with glaucoma who would otherwise have had a poor prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
262
4
32

Year Published

2000
2000
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 387 publications
(304 citation statements)
references
References 6 publications
6
262
4
32
Order By: Relevance
“…Viscoelastic is also injected into the region of excised sclera, or scleral lake, to prevent healing. 10 Both deep sclerectomy and viscocanalostomy involve fashioning of a partial thickness scleral flap, removing a second layer of sclera deep to the initial flap, and exposing Descemet's membrane. Schlemm's canal is unroofed during removal of the second, deep scleral layer.…”
Section: Introductionmentioning
confidence: 99%
“…Viscoelastic is also injected into the region of excised sclera, or scleral lake, to prevent healing. 10 Both deep sclerectomy and viscocanalostomy involve fashioning of a partial thickness scleral flap, removing a second layer of sclera deep to the initial flap, and exposing Descemet's membrane. Schlemm's canal is unroofed during removal of the second, deep scleral layer.…”
Section: Introductionmentioning
confidence: 99%
“…Many glaucoma surgical techniques have been developed in response to needs for achieving a lower pressure in glaucomatous patients (5,(26)(27)(28)(29)(30)(31)(32)(33)(34) . However, not only the mechanisms by which outflow facility is increased but also where exactly the flow is going remain a subject of intense study.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, various modifications were proposed, [3][4][5] yielding controversial results: several studies have shown that DS is comparable or less effective, [6][7][8][9][10][11] others that it is superior to standard TE in the treatment of open-angle glaucoma. 2,3 All authors described fewer early postoperative complications using this nonpenetrating technique than with TE. 3,[5][6][7]11 The dissection of the deep corneoscleral lamella is the most difficult part of the procedure.…”
Section: Introductionmentioning
confidence: 95%